Model Pembelajaran Techopreneur Meningkatkan Kemampuan Mahasiswa dalam Memulai Usaha di Universitas - John Roni Coyanda (Jurnal Informatika Global)
ABSTRACTTechnopreneur combining technology and entreprenur, Technopreneur is understanding the business of developing business with the ability to rely on science and technology, developed by the business Teknopreneur known as the business of technology. Business technology is developed with the occurrence of synergy between Teknopreneur as and business, University and Research as a new technology innovation center, and the Venture capitalist will fund the business.  University  in motivating the scholar to become the Businessman was very important in cultivating the number of businessmen. With the increase from the scholar's circle will reduce the increase in the number of unemployments in fact increased the number of fields on the work. His question was how the university side could make to Technopreneur. The role of his one it was explained by (Thomas Zimmerer) that one of the motive factors of the growth of entrepreneurship was entrepreneurship education. Moreover (Douglas A.Gray) suggested to begin efforts since early for example when still the lecture. Whereas the data in an empirical manner also was obtained through the research that was carried out to the student of the University about the factor most dominant motivated the alumnus to wirausahawan. Results of this research mentioned that the opportunity factor that pushed the dtudent and alumnus decided to become Technoprenur. With our success   get help from the Student's Program entrepreneurs we formed Technopreurship Center,yang could help the interested student in an effort to in the IT field.Keywords : Technopreneur, UniversityABSTRAKTechnopreneur merupakan gabungan teknologi dan wirausaha, Technopreneur  mengembangkan bisnis dengan kemampuan untuk menerapkan  ilmu pengetahuan dan teknologi, yang dikembangkan oleh usaha  Teknopreneur yang dikenal sebagai bisnis dengan teknologi. Bisnis teknologi dikembangkan dengan adanya sinergi antara Teknopreneur dan bidang usaha, Universitas sebagai pusat inovasi teknologi baru, dan bidang usaha besar   akan mendanai bisnis tersebut. Universitas dalam memotivasi sarjana untuk menjadi Pengusaha sangat penting dalam menumbuhkan jumlah pengusaha. Dengan bertambahnya dari peneliti dan usahanwan muda akan mengurangi peningkatan jumlah pengangguran bahkan meningkatkan jumlah bidang pada pekerjaan. Pertanyaannya adalah bagaimana pihak universitas dapat membuat Technopreneur. Peranannya dijelaskan oleh (Thomas Zimmerer) bahwa salah satu faktor pendorong pertumbuhan kewirausahaan adalah pendidikan kewirausahaan. Apalagi (Douglas A.Gray) menyarankan untuk memulai dari sejak dini misalnya saat masih proses perkuliahan. Sedangkan data secara empiris juga diperoleh melalui penelitian yang dilakukan kepada mahasiswa Universitas tentang faktor yang paling dominan memotivasi alumni untuk wirausahawan. Hasil penelitian ini menyebutkan bahwa faktor peluang yang mendorong mahasiswa dan alumni memutuskan untuk menjadi Technoprenur. Dengan kesuksesan kami mendapatkan bantuan dari para Program kreativias Mahasiswa, kami membentuk Technopreurship Center, yang dapat membantu mahasiswa yang tertarik dalam upaya di bidang TIKata kunci : Teknologi Wirausaha, Universitas